2019
DOI: 10.1038/s41467-019-08430-8
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic inverse vulcanization

Abstract: The discovery of inverse vulcanization has allowed stable polymers to be made from elemental sulfur, an unwanted by-product of the petrochemicals industry. However, further development of both the chemistry and applications is handicapped by the restricted choice of cross-linkers and the elevated temperatures required for polymerisation. Here we report the catalysis of inverse vulcanization reactions. This catalytic method is effective for a wide range of crosslinkers reduces the required reaction temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
308
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(326 citation statements)
references
References 54 publications
12
308
0
6
Order By: Relevance
“…The aliphatic chain provided by the stearic acid interacts strongly with the rubber, so that the rubber and sulfur components are held in close proximity on a molecular scale to facilitate interfacial interaction. Hasell recently reported that certain transition metal salts likewise facilitate the compatibility of previously unreactive olefins for successful inverse vulcanization …”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The aliphatic chain provided by the stearic acid interacts strongly with the rubber, so that the rubber and sulfur components are held in close proximity on a molecular scale to facilitate interfacial interaction. Hasell recently reported that certain transition metal salts likewise facilitate the compatibility of previously unreactive olefins for successful inverse vulcanization …”
Section: Resultssupporting
confidence: 60%
“…Some high‐temperature reactions of organics with elemental sulfur are known to produce H 2 S gas . Potential H 2 S evolution during preparation of ZOS 59‐99 was monitored by mass loss during reaction in conjunction with ELEM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that these capacities are related to amount of active sites available for mercury binding on the surface of the polymer. By increasing the surface area of these polymer materials (by foaming or preparing the polymers on a high surface area support, for instance), an increase in capacity is likely possible—a strategy that has been validated for other polymers made by inverse vulcanization 23. Finally, from the Freundlich model, the sorption intensity parameter ( n ) can be used to assess if the metal uptake is favorable.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there remains a need for sustainable and low‐cost mercury sorbents that can be easily prepared and deployed in areas with limited economic resources. To address this need, polymeric sorbents for mercury made from elemental sulfur and renewable plant oils have emerged as attractive materials 16–23. The plant‐derived monomers are renewable and there is a surfeit of sulfur produced during petroleum refining, so these polymers can be prepared sustainably and on a large scale 24.…”
Section: Introductionmentioning
confidence: 99%